Cultural affiliation is not enough: the repatriation of Ainu human remains - Nakamura, Naohiro (Cambridge University Press, 2017)
The challenges faced by indigenous peoples in repatriation negotiations vary across the globe. In 2012, three Ainu individuals launched a legal case against Hokkaido University, demanding the return of the human remains of nine individuals and a formal apology for having conducted intentional excavations of Ainu graveyards, stolen the remains and infringed upon their rights to perform ceremonies of worship. This action marked the first of such legal cases in Japan. The Ainu experienced both legal and ethical challenges during negotiations with the university; for example, while the claimants applied the Ainu concept kotan as a legal argument for collective ownership of the remains, Hokkaido University claimed the lack of assumption of rights relating to worship under the Civil Code of Japan. There has been significant progress recently on repatriation, mainly due to the Native American Graves Protection and Repatriation Act in the US, and several meaningful recommendations have been made to ease the repatriation process. However, such recommendations are often case specific and variations in the experiences of indigenous peoples from country to country have not been widely documented. This article discusses the challenges faced by the Ainu in repatriation negotiations in Japan, with a particular focus on the difficulties of applying indigenous customs and philosophies within legal frameworks.